The relationship of monetary dynamics and exchange rate in Malaysia / Ervinna Maslina Abd Muslikh Mashuri - Abd Muslikh Mashuri, Ervinna Maslina (2007)
This paper examines the existence of relationship of monetary dynamics and exchange rate in Malaysia that focus on demand for narrow and broad money balances. The objective of this study reveals the existence of a relationship among real money balances, real income, interest rate and exchange rate. The data for Malaysia are used as a case study. The variables used in this study are exchange rate (RM/USD), real income (GDP), and interest rate (T-bill) as independent variables and Narrow money (Ml) and Broad money (M2) as dependent variables. The quarterly period examined is 1994:Q3 — 2006:Q4 (50 observations). These studies use multiple regression models to investigate the relationship between real money balances and their determinants, exchange rate, real income and interest rate. Generally, results from testing the hypothesis of multiple regression models confirm that both money balances (real Ml and M2) have highly significant relationship with their determinants. Despite, interest rate has a significant contributor to narrow money (Ml) but not to broad money (M2). It is shown that the demand for money can be more stable by the inclusion of the exchange rate.